Northwest History. Alaska. Earthquakes & Volcanoes. (1936)
Alaska Feels Quake: Glacier Unaffected By Temblor. ALASKA FEELS QUAKE Glacier Unaffected by Temblor FAIRBANKS, Alaska, Feb. 25.— (AP)—Black Rapids Glacier, 130 miles southeast of here, groaned and thundered today, apparently unaccelerated by a sharp earthquake which was recorded on the University of Alaska seismograph last night. No damage was reported from the earth shock. The tremor was much sharper than one which sped the glacier's forward movement about thrio weeks ago, and Dr. Ervin S. Bramhall, university professor of physics, said he estimated the epicenter of last SfeJit's quake was within fifty miles of Fairbanks, and probably between here and the glacier. It was so severe during the forty seconds of its greatest amplitude that the agitated needle smeared the record so badly Dr. Bramhall was unable to ascertain definitely in what direction the quake centered. Mrs. H. E. Revell telephoned from the Black Rapids roadhouse that the quake was felt there, apparently of about the same intensity as in Fairbanks.